Simulation and assessment of the risk of carbon sink loss in Hubei Province, China - Li, Jiang; Ning, Baomiao; Shu, Rui; Xia, Yixiong; Yuan, Guobin; Shen, Yun; Yu, Yanping; Liang, Xun (Frontiers in Environmental Science, 2025)
IntroductionPredicting future land use/cover changes and their impact on carbon storage is crucial for achieving China's “Dual Carbon” goals. Current studies face challenges of low resolution and difficulties in fine-scale simulations.MethodThis study developed a novel large-scale, high-resolution approach for estimating and simulating carbon sinks and storage changes based on the PLUS model, incorporating cropland and grassland management practices' effects on soil organic carbon, and utilizing block parallel computing.Results and discussionResults show that from 2020 to 2030 and 2060, Hubei Province's croplands and construction lands are the main land types undergoing transition while forestlands steadily increase. Cropland management carbon sinks are highest under the natural development scenario. Grassland management carbon sinks are highest in the ecological priority scenario. Forest management carbon emissions peak under ecological priority. Based on simulation results, early warnings were issued to counties with high carbon sequestration and emission risks. The study proposes a high-resolution carbon stock estimation method and implementing large-scale risk warning systems. These findings provide crucial evidence for land policy formulation and achieving “Dual Carbon” goals, offering valuable data support for illegal land use regulation.